An urban dispersion inspired scenario for CFD model validation. (March 2021) - Brown, Alexander L.; Clemenson, Michael D.; Benson, Michael; Elkins, Christopher; Jones, Samuel T.
Abstract: Momentum, advection, diffusion, and turbulence are component physics relating to fire simulation tools like computational fluid dynamics (CFD). Magnetic Resonance Velocimetry and Magnetic Resonance Concentration MRV/MRC techniques can produce heretofore unrivaled detailed measurements of three-component velocity and concentration fields in turbulent flows. This study exhibits 3D flow comparisons between velocity and concentration fields obtained using MRC/MRV and SIERRA/Fuego for an urban geometry based on a section of downtown Oklahoma City. A 1:2500 scale water flow scenario provides 0.8 mm resolution data. Various techniques are employed to quantify the accuracy of the simulation results. The techniques all generally suggest a good comparison between the model and experiments throughout the compared volume. The selected metrics provide benchmark accuracy measures that can be used to indicate quantitative accuracy of the simulations, as well as for targets for future simulation improvements.